2022
DOI: 10.1029/2022gl100460
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Denman Glacier to Ocean Heat Flux Revealed by Profiling Float Observations

Abstract: Denman Glacier, which drains a marine‐based sector of the East Antarctic Ice Sheet with an ice volume equivalent to 1.5 m of global sea level rise, has accelerated and undergone grounding line retreat in recent decades. A deep trough and retrograde bed slope inward of the grounding line leave this glacier prone to marine ice sheet instability. The ocean heat flux to the ice shelf cavity is a critical factor determining the susceptibility of the glacier to unstable retreat. Profiling float observations show mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…MCDW intrusions have been observed on the East Antarctic continental slope (Bindoff et al, 2000;Foppert et al, 2019) and several parts of the continental shelf, including in the surroundings of the Totten Glacier (Williams et al, 2011;Rintoul et al, 2016;Silvano et al, 2017), the Denman Glacier (van Wijk et al, 2022), and the Amery Ice Shelf (Herraiz-Borreguero et al, 2015;Guo et al, 2022). Bottom temperatures simulated by WAOM (Figures 9D-F) are generally within the observed range, indicating MCDW intrusion in many locations of the East Antarctica sector.…”
Section: Water Mass Transformation Under the East Antarctica Ice Shelvesmentioning
confidence: 69%
“…MCDW intrusions have been observed on the East Antarctic continental slope (Bindoff et al, 2000;Foppert et al, 2019) and several parts of the continental shelf, including in the surroundings of the Totten Glacier (Williams et al, 2011;Rintoul et al, 2016;Silvano et al, 2017), the Denman Glacier (van Wijk et al, 2022), and the Amery Ice Shelf (Herraiz-Borreguero et al, 2015;Guo et al, 2022). Bottom temperatures simulated by WAOM (Figures 9D-F) are generally within the observed range, indicating MCDW intrusion in many locations of the East Antarctica sector.…”
Section: Water Mass Transformation Under the East Antarctica Ice Shelvesmentioning
confidence: 69%
“…In this region, the eddy conditions have recently been explored (FRE19; Stewart et al., 2018), wherein lateral tidal mixing is known to be weaker than that in the rest of the Antarctic margin (Padman et al., 2018), and the frontal structure of the ASC is relatively prominent (Pauthenet et al., 2021). The onshore CDW flux toward East Antarctica is collecting attention as a cause of glacial melting (e.g., van Wijk et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Geophysical observations have shown that extensive portions of the EAIS rest on bedrock below sea level (Fretwell et al., 2013). Oceanographic observations have demonstrated that relatively warm waters reach the calving fronts of glaciers that provide the major drainages of the EAIS, including the Totten Glacier (Rintoul et al., 2016; Silvano et al., 2017), the Vanderford Glacier (Herraiz‐Borreguero & Naveira Garabato, 2022; Ribeiro et al., 2021), and the Denman Glacier (Brancato et al., 2020; van Wijk et al., 2022). Satellite observations confirm that several glacier systems draining the EAIS have suffered ice mass loss, grounding line retreat, and acceleration of glacial flow (Rignot et al., 2019; Smith et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These observations have inspired new investigations of the vulnerability of the East Antarctic ice shelves to ocean‐driven melt, such as the Shackleton Ice Shelf (SIS)/Denman Glacier System (hereafter referred to as the Shackleton‐Denman System; Figure 1a), an area that is now receiving close attention from the scientific community (Herraiz‐Borreguero & Naveira Garabato, 2022; Urbini et al., 2010; van Wijk et al., 2022). The thinning of the SIS (Paolo et al., 2015) and retreat of the grounding line of the Denman Glacier (Brancato et al., 2020) may indicate an increase in ocean heat transport to the Shackleton‐Denman System.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation